2011
DOI: 10.1590/s0102-33062011000200003
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do solo contaminado com óleo diesel na estrutura da raiz e da folha de plântulas de Sebastiania commersoniana (Euphorbiaceae) e Schinus terebinthifolius (Anacardiaceae)

Abstract: Efeito do solo contaminado com óleo diesel na estrutura da raiz e da folha de plântulas de Sebastiania commersoniana (Euphorbiaceae) e Schinus terebinthifolius (Anacardiaceae) ABSTRACTEff ect of diesel contaminated soil on root and leaf of Sebastiania commersoniana (Euphorbiaceae) and Schinus terebinthifolius (Anacardiaceae)). Th e objective of this study was to evaluate whether the diesel contaminated soil alters the structure of the root and eophyll of S. commersoniana (Euphorbiaceae) and S. terebinthifoliu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In turn, the presence of an organic contaminant results in cell disruption as a direct effect on mitochondrial respiration or indirectly through cell growth and division (Issoufi et al, 2006), significantly altering the rate of cell division in cells. root apices, the size of the meristematic regions and the structure of the root hairs (Bona et al, 2011) further causing the adverse effects of diesel on root length to be reflected. These changes have been recorded in different species grown in contaminated soil, and it is considered that they are part of the adaptations that plants present to be able to develop under these stress conditions (Hernández-Ortega, 2014).…”
Section: Rootmentioning
confidence: 99%
“…In turn, the presence of an organic contaminant results in cell disruption as a direct effect on mitochondrial respiration or indirectly through cell growth and division (Issoufi et al, 2006), significantly altering the rate of cell division in cells. root apices, the size of the meristematic regions and the structure of the root hairs (Bona et al, 2011) further causing the adverse effects of diesel on root length to be reflected. These changes have been recorded in different species grown in contaminated soil, and it is considered that they are part of the adaptations that plants present to be able to develop under these stress conditions (Hernández-Ortega, 2014).…”
Section: Rootmentioning
confidence: 99%
“…Decrease in dry biomass of native Brazilian trees exposed to petroleum contaminated soils have been registered for S. terebinthifolius, Sebastiana commersoniana, Podocarbus lambertii, M. scabrella, M. pilulifera, M. caesapiniifolia and Eugenia uniflora [26,29,38]. However, other studies have concluded tolerance of Allophylus edulis, Campomanesia xanthocarpa, Podocarpus lambertii, Tibouchina granulosa and S. commersoniana to petroleum contaminated soils [21,24,[29][30][31].…”
Section: Diesel Phytotoxicitymentioning
confidence: 99%
“…Once contaminants are assimilated from the environment and translocated within plant tissues, they are transformed and/or stored by metabolic processes [17][18][19][20]. After the spill in the Araucaria Pine Forest, several investigations were elaborated to analyze the effect of the contaminated soil on the growth of native plant species and their potential for on-site phytoremediation application [21][22][23][24][25][26][27][28][29][30][31]. From these studies, native Brazilian trees that were tolerant to oil-contaminated soils were Mimosa caesalpiniifolia, Mimosa pilulifera, Sebastiana commersoniana and Schinus therebinthifolius.…”
Section: Introductionmentioning
confidence: 99%
“…These restrictions are revealed in various ways, such as decreased leaf area (Alves et al, 2018), biomass production (Zand et al, 2010), germination (Dib & Sadoudi Ali Ahmed, 2020), abnormal roots (Bellout, 2016), and atypical cell division (Salim et al, 2020). Moreover, research has demonstrated that roots in these contaminated soils tend to contract and branch out more (Bona et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated that roots in these contaminated soils tend to contract and branch out more (Bona et al, 2011).…”
mentioning
confidence: 98%